Factors Associated with Post-rewarming Procalcitonin Levels in Newborns with Hypoxic Ischemic Encephalopathy - Aslı Okbay Güneş; Aydın Bozkaya; Mehmet Emin Avlanmis (AVES Yayincilik, 2024)
Objective: To determine the factors associated with the procalcitonin levels in newborns with hypoxic-ischemic encephalopathy (HIE) who received therapeutic hypothermia (TH). Materials and Methods: The neonates, who had moderate/severe HIE and were treated with TH, were included. The neonates were arranged into 2 groups by procalcitonin (PCT) level after rewarming was completed. The neonates who had a procalcitonin level of < 2.5 ng/ml constituted Group 1 and the ones who had a procalcitonin level of ≥ 2.5 ng/ml constituted Group 2. Univariate and multivariate logistic regression was used to assess the factors related with PCT level. Results: The first group included 123 (87.9%) neonates and the second group included 17 (12.1%) neonates. The median gestational age was 38 (36-39) weeks and the mean birth weight was 3081.7 ± 552.8 grams. In group 2, the rates for severe HIE, cesarean section, antibiotic switch, convulsion, inotrope use and mortality were higher, and duration of hospitalization was longer, whereas Apgar scores were lower (P < .05). The risk of a high procalcitonin level was found to be 6-fold (95% CI 1.9-19.1) higher in severe HIE and 5.2-fold higher (95% CI 1.7-16) in cesarean delivery. Conclusion: In neonates with HIE/TH, high post-rewarming procalcitonin levels were related with severe HIE and cesarean delivery. Some other clinical and laboratory findings, which may reflect worse clinical status, were also associated with high procalcitonin levels.